Qualitative and quantitative analysis of prednisone chemical content in rheumatic herbs in Magelang Region - Riza Nur Afifah; Arief Kusuma Wardani; Tiara Mega Kusuma (Sasambo Journal of Pharmacy, 2025)
Currently, there is a phenomenon that shows that many herbs consumed by the public contain medicinal chemicals (BKO). This study aims to identify the presence of BKO prednisone in rheumatic herbs and its levels. This study took five types of samples of rheumatic herbs in Magelang area with different brands, namely samples of herbs A, B, C, D and E, which are available in capsule and powder form. Identification of prednisone in rheumatic herbs was carried out using thin layer chromatography (TLC) method with silica gel GF254 as stationary phase and ethyl acetate: chloroform mixture (4:1) as mobile phase. Quantitative analysis was performed using UV-Vis spectrophotometry with a maximum wavelength of 238.5 nm. The rf value of prednisone standard 0.42 was obtained and quantitative analysis showed that the prednisone content in sample B in the first replication was 3.22%, in the second replication was 2.18%, in the third replication was 2.23%.